The political timing of switching parties: an analysis of the party switching window law in Brazilian city councillors and its impacts on electoral performance - Thomé, Ruan Cursino (2024)
This research studies party-switching effects for Brazilian city councillors from 2008 to 2020. The research is focused on party-switching timing; while previous literature focuses mainly on members of parliaments, this research uses city councillors seeking re-election. To measure different timings, this research uses the introduction of a new Brazilian law that creates a party-switching window of thirty days that occurs six months before the election. Before, city councillors could only switch parties until one year before their next election. The results suggest that party switchers increased their chances of re-election after the introduction of the new law despite increased voter punishment.